'Pseudo' Treatment Failure of Pulmonary Tuberculosis in Association with a Tuberculoma. Issue 1 (3rd February 2000) - Long, Richard; Chomyc, Sylvia; Der, Evelina; Sitar, Daniel S
Abstract : Failure of tuberculosis patients to respond to treatment is usually explained by one or more of five mechanisms: improper drug prescription; patient nonadherence to prescribed therapy; primary or acquired drug resistance; drug malabsorption; and rarely, exogenous reinfection with a drug-resistant isolate. Response to treatment is best measured bacteriologically; two different smear and one culture criteria for failure are widely used. Patients meeting either smear, but not culture, criteria for treatment failure may be said to have 'pseudo' treatment failure. Whether a patient can meet both smear criteria for failure, and not have a mechanism for treatment failure nor meet culture criteria, is unknown. A case of 'pseudo' treatment failure is reported in which both smear criteria for failure were met, but no mechanism for failure was proven to be operative.